Requiem on Hippocratic Medicine or 20th Century Clinic as the Final Stage of Classic Medicine in Russia (Therapeutic and Pediatric Clinics Models) - Vladimir I. Borodulin; Valery Yu. Albitsky (Вопросы современной педиатрии, 2022)
The article is devoted to the end of the final (according to the authors) period in the development of classic medicine in Russia, that was based on principles dating back to the Hippocratic oath. Authors have concluded that the main paradigm has been changed from humanistic to market one after discussion of all the patterns and features of Russian medicine during XIX–XX centuries on the therapeutic and pediatric clinics models.